English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-27 04:47:00 · 4 answers · asked by parham 1 in Science & Mathematics Mathematics

4 answers

First: multiply the 1st & 3rd coefficient to get "-10." Find two numbers that give you "-10" when multiplied & "3" (2nd/middle coefficient) when added/subtracted. The numbers are: "5 and -2"

Sec: rewrite the expression with the new middle coefficients...

2x^2 + 5x - 2x - 5 = 0

*Factor - when you have 4 terms, group "like" terms...

(2x^2 - 2x) + (5x - 5) = 0
2x(x - 1) + 5(x - 1) =0
(x - 1)(2x + 5) = 0

Third: solve the two x-variables > set both parenthesis to "0"...

a. x - 1 = 0
*Add "1" to both sides...

x - 1 + 1 = 0 + 1
x = 1

b. 2x + 5 = 0
*Subtract "5" from both sides...

2x + 5 - 5 = 0 - 5
2x = -5

*Divide both terms by "2"...

2x/2 = -5/2
x = -5/2

Solutions: 1 and -5/2

2007-01-27 04:56:12 · answer #1 · answered by ♪♥Annie♥♪ 6 · 0 0

x=1

2007-01-27 13:00:24 · answer #2 · answered by tapoz360 1 · 0 2

I think

2x^2+3x-5=0
(x - 1)(2x + 5) = 0

if
x-1 = 0 , so X=1
or if
2x = -5 , so X = -2.5

I think that
God "Allah" help us.

2007-01-27 13:04:18 · answer #3 · answered by shamshona 2 · 1 0

(2x+5)(x-1)=0
2x+5=0
2x+5-5=0-5
2x=-5
x=-5/2
x-1+1=x+1
x=1

x=1,-5/2

2007-01-27 13:47:03 · answer #4 · answered by Dave aka Spider Monkey 7 · 0 0

fedest.com, questions and answers